The Influence of Apparatus Resource Development on the Effectivity of Population Administration Service in Cianjur Regency, West Java (Jurnal Bina Praja, 2018)
This study is based on a phenomenon which indicates that population administration in terms of the registration process; family card (KK) and identity card (KTP) in Cianjur District has not been effective, because the service is still slow, the procedure is complicated, not timely, and not transparent. The purpose of this study is to the influence of human resources (apparatus) development dimension on the effectiveness of population administration services. This research uses quantitative design, with a descriptive quantitative method that explains and describes the level of human resources (apparatus) development towards the effectiveness of population administration service in Cianjur Regency. Respondents were selected by using Proportional Stratified Random Sampling technique.  Primary data were collected through observation, questionnaires, and interviews; Respondents are apparatuses at the Department of Population and Civil Registry as well as apparatuses from 18 Sub-districts in Cianjur regency as many as 187 samples. Secondary data were obtained through study documentation. Data were analyzed by Structural Equation Model (SEM). The results show that the development of human resources (apparatus), including learning, education, development, and training dimension has positively affected the effectiveness of population administration services significantly. The research concluded that the influence of human resource development on the effectiveness of the population administration service in Cianjur Regency is determined by the dimensions of learning, education, development, and training. These influences imply that the four dimensions of human resource development (apparatus) have important roles in the effectiveness of population administration services in Cianjur Regency.
Keywords: Human Resources; Service Effectiveness; Population Administration